RESEARCH PARADIGM AND THE PHILOSOPHICAL FOUNDATIONS OF A QUALITATIVE STUDY - Kamal, Siti Soraya Lin Binti Abdullah (PEOPLE: International Journal of Social Sciences, 2019)
This paper principally describes the link between the research paradigm (constructivism) and the philosophical basis (ontology, epistemology and methodology) of a qualitative study. This article begins with an overview of qualitative study which consists of its meanings and features followed by the definition of research paradigm. The constructivist paradigm is explained alongside the example of my own qualitative research project. This paper also discusses how the constructivist paradigm relates to the ontology, epistemology and methodology of a qualitative study. It is hoped that this article will facilitate novice researchers particularly to know what the meaning of each philosophical term is, how the research paradigm is interwoven within the philosophical basis of a qualitative research and how different research paradigms serve different research purposes.